Longitudinal analysis of culture of patient safety survey results in surgical departments - Butler, Logan R.; Lashani, Shaian; Mitchell, Cody; Ra, Jin H.; Greenberg, Caprice; Marks, Lawrence B.; Ivester, Thomas; Mazur, Lukasz (Frontiers in Health Services, 2024)
BackgroundThere is a need for improved methodologies on how to longitudinally analyze, interpret and learn from the Surveys on Patient Safety Culture™ (SOPS), developed by the Agency for Healthcare Research and Quality (AHRQ). Typically, SOPS quantify results by the percentage of positive responses, but this approach may miss insights from neutral or negative feedback.Study designThe SOPS were distributed every two years from 2011 to 2022 to all hospital staff at one academic institution from perioperative services. Differences between rates of “positive” and “negative” scores (“Delta”), and “neutral” responses over time were calculated. The coefficient of determination (R2) was used to assess the correlation strength of the positive scores as the primary outcomes provided by the SOPS and Delta values over time. Finally, we evaluated patterns (crossing and converging [indicating “worrisome” patterns] vs. diverging [suggesting “desirable” pattern] vs. stable [suggesting “neutral” pattern]) of the longitudinal scores.ResultsA total of 1,035 responses were analyzed [51 and 40 survey items for SOPS v1 and v2 (2022 only), respectively]. Comparing the R2 values of the positive only scores to the Delta scores demonstrated a change in effect size for “Nonpunitive Response to Error” (R2 = 0.290 vs. 0.420). Of the 13 specific categories measured through SOPS, plotting negative vs. positive values elucidated 2 crossing, 2 converging and 2 diverging patterns indicating both a decrease in positive responses and an increase in negative responses rather than neutral.ConclusionLongitudinal analysis of the SOPS using the directional measures, Delta and pattern trends can provide organizations with additional key insights regarding culture of patient safety.